Numerical Solution of Seventh-Order Boundary Value Problems by a Novel Method - İnç, Mustafa; Akgul, Ali (Hindawi Ltd, 2014)
We demonstrate the efficiency of reproducing kernel Hilbert space method on the seventh-order boundary value problems satisfying boundary conditions. These results have been compared with the results that are obtained by variational iteration method (VIM), homotopy perturbation method (HPM), Adomian decomposition method (ADM), variation of parameters method (VPM), and homotopy analysis method (HAM). Obtained results show that our method is very effective.
Keywords: Efficient Computational Method; Laplace Decomposition Method; Reproducing Kernel; Algorithm; Equation